Special features of the greening of Ginkgo biloba L. - Skribanek, Anna; Solymosi, Katalin; Böddi, Béla (Acta Biologica Szegediensis, 2005)
Most studies on chlorophyll biosynthesis and greening are carried out on angiosperm leaves. Unlike angiosperms, most gymnosperms can synthesize chlorophyll in the dark and cannot be etiolated. Ginkgo (Ginkgo biloba L.) is an exception. In this work, the greening of the stems and the leaves of ginkgo were analyzed. Pigment content changes, changes in the 77 K fluorescence emission spectra and plastid ultrastructure were studied and compared at different temperatures.